Creative Communication through the Analogy of Phishing-Fishing and Slogan “Don’t Know? Kasih No!” - Sukardi, Cindy Fransisca; Himawan, Muhammad Noor Rahman; Marta, Rustono Farady; Panggabean, Hana; Wang, Changsong (Universitas Negeri Medan, 2025)
Rapid technological developments are causing technological information to be progressively integrated into human life. However, this development was followed by various challenges and problems, including phishing. Providing education on how to deal with phishing practices is important to do as a way of raising awareness among internet users. This attempt requires the role of various parties, including banking institutions in Indonesia, such as Bank Central Asia, that are committed to raising public awareness through a video entitled “Jangan Mau Jadi Korban Penipuan Online. Don’t Know? Kasih No!”. Each element contained was studied using qualitative research methods, Umberto Eco’s semiotics analysis, to see the relationship between language and symbols, with an interpretation based on the elements of pentad dramatism. The result shows the advertisement contains act, scene, agent, agency, purpose of communicating messages through language and symbols in form of creative analogy of fishing-phishing and “Don’t Know? Kasih No!” slogan that consistently represents feeling of humor and nostalgia.